2002
DOI: 10.1002/1099-0682(200203)2002:3<678::aid-ejic678>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Alkyl(amino)- and Alkyl(chloro)phosphanyl-Substituted Cyclopentadienyl Complexes of Titanium and Zirconium

Abstract: Keywords: Titanium / Zirconium / Cyclopentadienyl ligands / P ligands / PolymerisationPhosphanyl-substituted cyclopentadienes of the type [R n Cp−PR(NR 1 R 2 /Cl)] (1−22) (R = Alk, Ar; R 1 , R 2 = H, Alk, Ar, SiR 3 ; R n Cp = tBuCp, Me 4 Cp, Ind, Me 6 Ind, Flu) can be synthesised by reaction of alkyldichlorophosphanes and alkyl(amino)chlorophosphanes with alkali metal cyclopentadienides. The method used is a general one and provides high isolated yields of the target compounds. The phosphanylcyclopentadienes c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…(4)). [C 5 Me 4 P( t Bu)(NEt 2 )]TiCl 3 was previously made in a similar way from Me 3 SnC 5 Me 4 P( t Bu)(NEt 2 ) and TiCl 4 [30]. Complex 4 crystallizes with the extended structure shown in Fig.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…(4)). [C 5 Me 4 P( t Bu)(NEt 2 )]TiCl 3 was previously made in a similar way from Me 3 SnC 5 Me 4 P( t Bu)(NEt 2 ) and TiCl 4 [30]. Complex 4 crystallizes with the extended structure shown in Fig.…”
Section: Synthesismentioning
confidence: 99%
“…2), e.g. (C 5 H 5 )TiCl 3 [34], [C 5 Me 4 P( t Bu)(NEt 2 )]TiCl 3 [30], and (C 5 Me 4 -CH 2 CH 2 Ph)TiCl 3 [35] ( Table 4). The three independent Ti Ã/C bond lengths are 2.306 (2) …”
Section: (C 5 Me 4 H)ticl 3 (5)mentioning
confidence: 99%
“…99 In an analogous manner, treatment of (Cp-P-t-BuCl) 2 CMe 2 with one equivalent of TiCl 4 in the presence of Et 3 N gives complex [(Cp-P-t-BuCl) 2 CMe 2 ]TiCl 2 . 101 Cationic ansa-(η 5 -cyclopentadienyl)(η 6 -arene) titanium derivatives have been prepared with both Cp and Cp * derivatives. Treatment of TiCl 4 with C 5 H 4 (R)SiMe 3 (R = CMe 2 Ph, CMe 2 CH 2 Ph, CHPh 2 ) gives the corresponding half-sandwich complexes (η 5 -C 5 H 4 R)TiCl 3 Alkylation of (η 5 -C 5 H 4 R)TiCl 3 gives (η 5 and two-carbon bridges.…”
Section: Ansa-metallocenesmentioning
confidence: 99%
“…209 Treatment of (t-BuCpP(-t-Bu)Cl)TiCl 3 with LiN(H)-t-Bu in the presence of Et 3 N leads to the formation of the constrained geometry complex (η 5 :η 1 -tBuCpP(-t-Bu)N-t-Bu)TiCl 2 in high yield. 101 Constrained geometry complexes with other π ligands have also been prepared. Treatment of (4-Dimethylsilyl-tertbutylamido)-N ,N -diisopropyl-1-aminoboratabenzene with two equivalents of t-BuLi followed by treatment with TiCl 4 gives (4-Dimethylsilyl-tert-butylamido)-N ,N -diisopropyl-1-aminoboratabenzene titanium dichloride complexes (46).…”
Section: Ti CLmentioning
confidence: 99%
“…About the ligand of phosphinoamide, Roesky et al [18] reported homoleptic phosphinoamide complexes of lanthanide. Recently, Kotov et al [19] reported the phosphorusbridged Cp-amide Ti complex, which produced linear, high-molecular-weight PE with an activity of 10 5 g/ (mol Ti h bar). We have also prepared a series of nonbridged phosphinoamide cyclopentadienyl complexes of titanium.…”
Section: Introductionmentioning
confidence: 98%